Flexible Workplace Practices: Employees’ Experiences in Small IT Firms - Gordon, Catherine (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
This paper examines how employees experience flexible workplace practices (FWPs), such as flex-time, in the context of small firms. Past research consistently documents that employees’ experiences vary according to whether or not the workplace culture is supportive of FWPs and work-life balance needs. Studies, however, typically use individual level data or focus on large companies. Little research has focused on the experiences of employees of small firms. Possibly, employees of small firms have somewhat unique experiences of FWPs because of the workplace context. Like past research, this paper considers how gender and age relations structure the workplace. Also taken into account are the control strategies that management employs over the workforce.Data are taken from a Canadian study on small information technology (IT) firms that employed between four and 21 individuals. A multiple case study of 17 firms is conducted using web-surveys, semi-structured interviews, case study reports, field notes, and HR policy documents. Three different workplace contexts emerged among study firms based on their flexibility and workplace culture with respect to time. Some of these workplaces reproduced hegemonic gender, age, and class expectations, whereas others somewhat challenged them. The three firm-types did not vary according to firm-specific characteristics, such as business specialization, but patterns with regard to age and gender characteristics of the owners and employees were evident. Employees’ experiences varied according to where they worked. The findings suggest that similar and different processes occur in small firms compared to the large companies often studied in the literature. Like large firms, small firms are not neutral or based on a consensus. Small firm employees, however, may be considerably more vulnerable.